Pedagogical aspects of development of music minimalism (Pedagogy of Higher and Secondary Education, 2006)
Pedagogical aspects of development of music minimalism. The paper is devoted to the characteristic of the didactical bases of music of minimalism - as creativity of the composers, and of performans style. An harmonical orientation of symbolics and extatic of minimalism acctened tn conditionality of his meaning by structure of archetypes.
Keywords: minimalism; mtnimalisation of composition; consonance emancipation; repetition